1988
DOI: 10.1007/bf00176855
|View full text |Cite
|
Sign up to set email alerts
|

Morphine induces delayed anorexia in rats

Abstract: The delayed suppression of feeding caused by morphine was investigated in the rat. A single injection of morphine evoked a triphasic influence on feeding: a brief (1 h) severe anorexia was followed by hyperphagia (3 h) and a mild (20%) yet persistent (4-24 h) anorexia. This latter anorexic effect was at least partially naltrexone reversible, and the duration of this antagonism (8 h) was longer than that of naltrexone's anorexic effect (4 h). Delayed morphine anorexia cannot be ascribed to morphine's initial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Most reports about the relation between beta-endorphin and food intake showed that the injection of beta-endorphin stimulated appetite. However, some reports suggest that injection of morphine, an agonist of opioid receptor, at a high dose suppressed food intake in rats (Blundell and Leshem 1974;Leshem 1981;Leshem 1988;Wolgin and Benson 1990;Wolgin and Benson 1991). Supporting these reports, in one study the feeding behavior in beta-endorphin-deficient mice was more enhanced than that in normal mice (Appleyard et al 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Most reports about the relation between beta-endorphin and food intake showed that the injection of beta-endorphin stimulated appetite. However, some reports suggest that injection of morphine, an agonist of opioid receptor, at a high dose suppressed food intake in rats (Blundell and Leshem 1974;Leshem 1981;Leshem 1988;Wolgin and Benson 1990;Wolgin and Benson 1991). Supporting these reports, in one study the feeding behavior in beta-endorphin-deficient mice was more enhanced than that in normal mice (Appleyard et al 2003).…”
Section: Discussionmentioning
confidence: 86%
“…In rodents, both hyperphagia [21–23] and anorexia [24–30] have been reported depending on the dose and treatment regimen of morphine (reviewed in [31]). Leshem [27, 32] showed that morphine has a triphasic effect on feeding. Following injection of 15 mg/kg, morphine suppressed intake during the first h, enhanced intake during the next 3 h, and then suppressed intake again for up to 24 h. In humans, opioid agonists such as methadone and butorphanol tartrate stimulated food intake, while naloxone, an opioid antagonist, acutely reduced food intake in obese or lean humans.…”
Section: Discussionmentioning
confidence: 99%
“…Morphine has also been shown to have a triphasic effect on feeding (Leshem, 1981, Leshem, 1988). Following injection of 15 mg/kg, morphine suppressed intake during the first h, enhanced intake during the next 3 h, and then suppressed intake again for up to 24 h. These studies were all performed prior to the discovery of many of the appetite-regulating pathways uncovered in the last 20 years.…”
Section: Discussionmentioning
confidence: 99%